Distinctive Patterns of Initially Presenting Metastases and Clinical Outcomes According to the Histological Subtypes in Stage IV Non-Small Cell Lung Cancer. Issue 6 (February 2016) - Lee, Dong Soo; Kim, Yeon S.; Kay, Chul S.; Kim, Sung H.; Yeo, Chang D.; Kim, Jin W.; Kim, Seung Joon; Kim, Young K.; Ko, Yoon H.; Kang, Jin H.; Lee, Kyo Y.
Abstract : Abstract: This study was designed to compare the primary patterns of metastases and clinical outcomes between adenocarcinoma (Adenoca) and squamous cell carcinoma (SQ) in initially diagnosed stage IV non-small cell lung cancer (NSCLC). Between June 2007 and June 2013, a total of 427 eligible patients were analyzed. These patients were histologically confirmed as Adenoca or SQ and underwent systemic imaging studies, including 18F-fluorodeoxyglucose positron emission tomography/computed tomography and brain imaging. Synchronous metastatic sites were categorized into 7 areas, and whole-body metastatic scores were calculated from 1 to 7 by summation of each involved region. We compared the patient, tumor, and metastatic characteristics according to the histological subtypes, and examined clinical outcomes. The enrolled study cohort comprised 81% (n = 346) Adenoca patients and 19% (n = 81) SQ patients. The median age of the study population was 65 years (range, 30–94 years), and 263 (61.6%) patients were male. The most common metastatic sites were thoracic lymph nodes (LNs) (84.3%), followed by lung to lung/lymphangitic spread (59%) and bone (54.8%). The distribution of patient characteristics revealed that age ≥65 years (69.1% vs 50.6%; P = 0.003) and male sex (84% vs 56.4%; P < 0.001) were more frequently found in SQ patients. Regarding metastatic features, bone metastasis (60.4% vs 30.9%; P < 0.001), lung to lung/lymphangitic metastasis (63% vs 42%; P = 0.001), and brain metastasis (35% vs 16%; P = 0.001) were significantly and more frequently found in Adenoca patients. Patients with high metastatic scores (score 3–6) were more frequently found to have Adenoca (91.6% vs 73.4%; P < 0.001). In multivariate prognostic evaluation, sex ( P = 0.001), age ( P < 0.001), histology ( P < 0.001), LN status ( P = 0.032), pleural/pericardial metastasis ( P = 0.003), abdomen/pelvis metastasis ( P < 0.001), axilla/neck metastasis ( P = 0.006), and treatment factors ( P < 0.001) remained independent prognostic factors affecting overall survival. We observed distinctive patterns of primary metastases and clinical outcomes according to the histological subtypes in stage IV NSCLC. Future studies need to disclose the underlying mechanism of these unique metastatic features and tumor biologies.